Virtual patient simulation in an interactive educational module on intimate partner violence: nursing students’ experiences—a mixed-methods study - Eckerström, Joachim; Mårtensson, Sophie; Larsson, Margaretha; Knez, Rajna; Ljudvåg, Madeleine; El Alaoui, Samir; Dahlström, Karin; Elvin Nowak, Ylva; Stenfors, Terese; Jayaram-Lindström, Nitya; Kristiansson, Marianne; Fors, Uno; et al. (Frontiers in Digital Health, 2025)
BackgroundMultiple studies have shown that healthcare professionals often feel uncertain about when to inquire about intimate partner violence (IPV), the appropriate methods for doing so, and how to respond to the answers. Virtual patient (VP) cases are an interactive educational tool that can be effective for learning and training clinical reasoning skills. However, there is a lack of research on the use of VP in psychiatry education. This study aimed to investigate nursing students' experiences of using a VP as part of an educational module, integrated into their foundational training on IPV during their nursing education.MethodsThe study employed a mixed-methods approach, incorporating both quantitative and qualitative data. Participants (N = 62) completed an interactive educational module on IPV, in three consecutive parts: (a) a web-based education on IPV, (b) training with a VP, and (c) a seminar for follow-up discussions.ResultsThe VP platform was considered user-friendly and easy to navigate, although some participants found the instructions challenging. Participants perceived the VP as beneficial for learning about IPV and for practicing interactive patient dialogues. They appreciated the rich set of questions and the feedback provided, both by the experts in the field of IVP and by the VP itself. However, some participants noted that interacting with a VP on a screen was less emotional compared to real human interactions.ConclusionThe interactive educational module, integrated into the regular nursing program, was positively received by the students. Overall, the VP was considered beneficial for learning about IPV, easy to navigate, and provided a valuable opportunity for practice.